Організація паралельних обчислень для локального оцінювання якості функціонування складних систем - Поліщук, О.Д.; Тютюнник, М.І.; Яджак, М.С. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The parallel-consecutive approach to optimization of calculations for local estimation of quality of functioning of the complex dynamical systems is proposed. This approach is oriented on realization on universal parallel calculational means with common memory.